1976
DOI: 10.1148/120.2.283
|View full text |Cite
|
Sign up to set email alerts
|

Intrathoracic Manifestations of Amyloid Disease

Abstract: Nine cases of intrathoracic amyloid disease have been reviewed. A brief summary of historical material is presented along with detailed descriptions of the more pertinent cases. Observations suggest that a classification of the radiographic manifestations is needed with stress on massive calcific lymph node enlargement and a pulmonary lesion characterized by aggregations of small nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
2
7

Year Published

1982
1982
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 8 publications
1
16
2
7
Order By: Relevance
“…Wilson et al reported that chest CT occasionally reveals coarse calcifications in enlarged lymph nodes caused by amyloid protein deposition (2). Calcification, however, is not specific to amyloid lymphadenopathy, and, in fact, our case showed no calcification on CT. Amyloid lymphadenopathy is difficult to differentiate from lymphadenopathy caused by other diseases on imaging studies, including CT.…”
Section: Discussioncontrasting
confidence: 67%
“…Wilson et al reported that chest CT occasionally reveals coarse calcifications in enlarged lymph nodes caused by amyloid protein deposition (2). Calcification, however, is not specific to amyloid lymphadenopathy, and, in fact, our case showed no calcification on CT. Amyloid lymphadenopathy is difficult to differentiate from lymphadenopathy caused by other diseases on imaging studies, including CT.…”
Section: Discussioncontrasting
confidence: 67%
“…A second mechanism is increased fragility and disruption of the alveolar walls as a result of amyloid deposits on alveolar wall [9]. The third mechanism is ischaemia leading to destruction of alveolar walls as a result of amyloid deposition around capillaries and within the interstitial tissue, ultimately obliterating alveolar capillaries [9].…”
Section: Discussionmentioning
confidence: 99%
“…(15) Also, due to the nonspecific appearance of pulmonary amyloidosis, diagnosis requires histological confirmation. Congo red staining produces characteristic apple-green birefringence under polarised light in the presence of amyloidosis.…”
Section: Case Reportmentioning
confidence: 99%